Spatial Variation and Contamination Levels of Different Metals in Soils of Bangladesh Sundarbans - Ataullah, Md.; Hoque, Sirajul; Rashid, Parveen; Ahmed, Ashfaque (Indian Forester, 2018)
Soil samples were collected from thirteen different locations of the Sundarban mangrove forests (SMF) of Bangladesh. Eight different metals were analyzed and the mean value of Na, K, Ca, Mg, Mn, Fe, Zn and Pb content were 214.4 , 22.17 , 1.02 , 2.74 , 0.77, 4.76, 0.04 and 0.53 mg/kg respectively were estimated. The concentrations of studied metals found in surface sediments were significantly higher than those from the local background. Enrichment factors (EF), geoaccumulation index (Igeo), potential contamination index (Cp) and statistical analysis showed that the heavy metals in SMF pose ecological risks. The studied metals in the soil samples were signi?cantly correlated with one another. Enrichment factor values of the soil samples revealed that most of the soil samples were moderate to extremely severe enriched by heavy metals. The Igeo values and Cp values of the soil samples revealed that the soils of SMF were moderately contaminated by Pb. It seemed that heavy metals occur in SMF largely due to the anthropogenic activities. Principle component analysis (PCA) showed the cluster formation between Pb and Zn, and between Mg and Ca. The study provides the present status of different metals of Bangladesh Sundarbans.